A porous nanofiber gas diffusion layer and its preparation method and application
The porous nanofiber gas diffusion layer is prepared through electrospinning technology and post-treatment, which solves the problem of high equipment requirements for the gas diffusion layer preparation process in the prior art, and realizes a gas diffusion layer with high porosity and hydrophobic properties, improving the performance of fuel cells.
Patent Information
- Application Number
- CN202410680532.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-29
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-05-29
AI Technical Summary
The gas diffusion layer preparation process in existing fuel cells has high requirements for equipment, resulting in the lag in the development of domestic gas diffusion layers and lack of effective solutions.
The nanofiber gas diffusion layer is prepared by electrospinning technology, and its porosity and hydrophobic properties are improved through post-treatment operations.
The high porosity and hydrophobic properties of the porous nanofiber gas diffusion layer are achieved, and the mass transfer performance and electrochemical properties of the fuel cell under high current density are improved.
Smart Images

Figure CN118412483B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of fuel cells or electrolytic cells, and in particular to a porous nanofiber gas diffusion layer and a preparation method and application thereof. Background Art
[0002] Proton exchange membrane fuel cells will be widely used in the transportation field, fixed power stations, etc. in the future due to their high energy conversion efficiency, low pollution, fast start-up and other application advantages. Generally speaking, a single cell of a proton exchange membrane fuel cell is composed of key components such as the cathode / anode gas diffusion layer, the cathode / anode catalyst layer, and the electrolyte membrane. Each component is closely related to the performance, cost and stability of the proton exchange membrane fuel cell.
[0003] As one of the key components of proton exchange membrane fuel cells, the gas diffusion layer plays a role in mass transfer, electrical conduction, and heat conduction in proton exchange membrane fuel cells. Its optimization will inevitably promote the development of proton exchange membrane fuel cells. Generally speaking, the gas diffusion layer of a proton exchange membrane fuel cell consists of two parts: a microporous layer and a support layer. The support layer is mostly carbon fiber paper or carbon fiber cloth, and the microporous layer is a porous layer formed by a mixture of carbon powder, hydrophobic materials, etc. At present, the commercial gas diffusion layers are mainly the Toray series produced by Toray Corporation of Japan and the SGL series produced by Gothenburg Company of Germany. In recent years, many domestic companies have also been developing gas diffusion layers to free them from the shackles of foreign products, but there is still a lack of effective gas diffusion layers. The reason is that the preparation process of the gas diffusion layer has high requirements for equipment. Summary of the invention
[0004] One of the purposes of the present invention is to provide a method for preparing a porous nanofiber gas diffusion layer.
[0005] The second object of the present invention is to provide a porous nanofiber gas diffusion layer prepared by the above preparation method, which has a gradually hydrophobic property.
[0006] The third object of the present invention is to provide the application of the porous nanofiber gas diffusion layer, which can be used in proton exchange membrane fuel cells and other fuel cells.
[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0008] In a first aspect, the present invention provides a method for preparing a porous nanofiber gas diffusion layer, comprising the following steps:
[0009] (1) The core layer dispersion is prepared as follows: prepare 50-150 g / L polyacrylic acid solution, stir for 30-180 min, then add ionomer powder, stir for 30-180 min, let stand for 10-30 min, and obtain a uniform polymer solution for use; prepare 100-200 g / L acetylene black dispersion, ultrasonicate for 30-180 min, and obtain a uniform carbon powder solution; mix the polymer solution and the carbon powder solution at a volume ratio of 0.5-2:0.5-1.0, and stir for 60-240 min to obtain a core layer dispersion;
[0010] (2) Preparation of the shell solution: prepare 50-150 g / L polyacrylic acid solution, stir for 30-180 min, then add an equal volume of 60% polytetrafluoroethylene dispersion, stir for 30-180 min, and let stand for 10-30 min to obtain a shell solution;
[0011] (3) Preparation of nanofiber gas diffusion layer, specifically as follows: placing core layer dispersion and shell layer solution in syringes respectively, and obtaining nanofiber gas diffusion layer by electrospinning;
[0012] (4) The post-treatment operation of the nanofiber gas diffusion layer is as follows: the gas diffusion layer is placed in a closed device and the temperature of the device is raised to 60-90°C; nitrogen gas with a humidity of 60-100% is introduced at a nitrogen flow rate of 30-2000 mL min -1 , the passage time is 24~48h, and a porous nanofiber gas diffusion layer is obtained.
[0013] The electrospinning parameters in step (3) are as follows: the flow rate of the shell solution is controlled to be 0.02-1.5 mL•min -1 , control the flow rate of the core layer dispersion to 0.02~2.5mL•min -1 , set the voltage of the regulated power supply to 10~18kV, and the distance between the spinning needle and the receiver to 10~25cm.
[0014] The ionomer in step (1) is selected from perfluorosulfonic acid resin, perfluorosulfonic acid doped polypyrrole, perfluorosulfonic acid doped polyaniline, sulfate doped polypyrrole, sulfate doped polyaniline, dodecylbenzenesulfonic acid doped polypyrrole, dodecylbenzenesulfonic acid doped polyaniline, phosphotungstic acid, etc.
[0015] In a second aspect, the present invention provides a porous nanofiber gas diffusion layer prepared by the above preparation method.
[0016] The porous nanofibers of the gas diffusion layer are composed of a multi-layer structure. The core layer is composed of nanofibers with electronic conductivity, forming an electronic conduction channel of the gas diffusion layer. The first shell layer outside the core layer is composed of polytetrafluoroethylene and carbon material, which can conduct electrons and accommodate a part of liquid water, so that the gas diffusion layer has moisture retention ability. The second shell layer is a polytetrafluoroethylene layer, which has a hydrophobic function and can discharge liquid water out of the body.
[0017] In a third aspect, the present invention provides a fuel cell comprising the porous nanofiber gas diffusion layer.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] 1. The porous nanofiber gas diffusion layer of the present invention has a relatively high porosity of 0.75-0.92, which is conducive to the reaction gas entering the gas diffusion layer.
[0020] 2. The porous nanofibers of the porous nanofiber gas diffusion layer of the present invention are composed of a multilayer structure. The core layer is composed of nanofibers with electronic conductivity, forming an electronic conduction channel of the gas diffusion layer. The first shell layer outside the core layer is composed of polytetrafluoroethylene and carbon materials, which can conduct electrons and accommodate a portion of liquid water, so that the gas diffusion layer has moisture retention ability. The second shell layer is a polytetrafluoroethylene layer, which has a hydrophobic function and can discharge liquid water from the body. In this way, under low humidity conditions, since the first shell layer can accommodate a portion of liquid water, it can play a role in humidifying the gas, so that the battery has higher electrochemical performance. Under high humidity or during product transmission, the second shell layer can discharge excess liquid water from the body to avoid the generation of a large amount of liquid water under high current density to affect the gas transmission process, thereby causing the battery performance to decline.
[0021] 3. The fuel cell assembled with the porous nanofiber gas diffusion layer of the present invention has good mass transfer performance in the high current density region. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 Schematic diagram of nanofiber preparation device, wherein 1 is polymer solution, 2 is carbon powder dispersion, 3 is core-shell spinning needle, 4 is injection tube, 5 is spinning needle, and 6 is receiver.
[0023] Figure 2 Schematic diagram of nanofiber post-processing device, wherein 1 is gas inlet, 2 is gas outlet, 3 is sealing frame, 4 is gasket, 5 is nanofiber gas diffusion layer, and 6 is screw accessories.
[0024] Figure 3 This is a schematic diagram of the structure of the porous nanofiber gas diffusion layer prepared in Example 1.
[0025] Figure 4 Contact angle images of gas diffusion layers: (a) commercial gas diffusion layer SGL 29BC; (b) porous nanofiber gas diffusion layer prepared in Example 1.
[0026] Figure 5 This is the discharge performance diagram of the proton exchange membrane fuel cell assembled with porous nanofiber gas diffusion layer. The comparison sample is the performance of a single cell assembled with SGL29BC. DETAILED DESCRIPTION
[0027] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0028] Example 1
[0029] A method for preparing a porous nanofiber gas diffusion layer comprises the following steps:
[0030] (1) Preparation of the core layer dispersion: 500 mg of polyacrylic acid was weighed and dissolved in 10 mL of deionized water, stirred for 30 min, then 500 mg of perfluorosulfonic acid resin was added, stirred for 30 min, and allowed to stand for 30 min to obtain a uniform polymer solution for use; 1000 mg of acetylene black was weighed and dispersed in 10 mL of deionized water, ultrasonicated for 120 min to obtain a uniform carbon powder solution; 1.0 mL of the polymer solution and 1.0 mL of the carbon powder solution were taken, the two were mixed evenly, and stirred for 240 min to obtain a core-shell dispersion.
[0031] (2) Preparation of the shell solution: weigh 500 mg of polyacrylic acid and dissolve it in 10 mL of water, stir for 30 min, then add 10 mL of 60% polytetrafluoroethylene dispersion, stir for 120 min, and let stand for 30 min to obtain a shell solution.
[0032] (3) Preparation of nanofiber gas diffusion layer, as follows:
[0033] (a) Construction of nanofiber preparation device, such as Figure 1 As shown, the core layer dispersion and the shell layer solution are placed in 5 mL syringes respectively, and then the syringes are placed on syringe pumps respectively to control the flow rate of the liquid in the syringe tubes; the two syringes are connected to the syringe tube 4 respectively, and then the syringe tube 4 is connected to the core-shell spinning needle 3, and then the core-shell spinning needle 3, the syringe tube 4, and the spinning needle 5 are connected, and the stabilized power supply connector is connected to the spinning needle 5;
[0034] (b) Adjust the shell injection pump flow rate to 0.02 mL•min -1 The flow rate of the nuclear layer injection pump is 0.02 mL•min -1, then the solution in the injection tube 4 coming out of the core-shell spinning needle 3 is a mixed solution, with a carbon powder dispersion inside and a polymer solution outside. Since both the carbon powder dispersion and the polymer solution are aqueous solutions, at the interface region between the two, under the action of the concentration gradient, the carbon powder and ionomer materials diffuse from the inside to the outside, while the polytetrafluoroethylene diffuses from the outside to the inside, so that the solution entering the spinning needle 5 has a gradient distribution of hydrophobic materials from the outside to the inside. The voltage of the stabilized power supply is set to 10 kV, the distance between the spinning needle 5 and the receiver 6 is 10 cm, and a nanofiber gas diffusion layer is obtained on the surface of the receiver 6.
[0035] (4) The post-treatment operation of the nanofiber gas diffusion layer is as follows: the gas diffusion layer is placed in a sealed apparatus (structured as Figure 2 The device was heated to 60°C and nitrogen with a humidity of 60% was introduced into the instrument at a nitrogen flow rate of 30 mL min -1 , the passage time is 24h. When nitrogen containing water vapor passes through the nanofiber gas diffusion layer, liquid water is distributed along the nanofibers. Since polyacrylic acid is easily soluble in aqueous solution, the polyacrylic acid in the nanofibers will be discharged with the nitrogen, so that the nanofibers present a porous structure, that is, a porous nanofiber gas diffusion layer with a diameter of 140nm and a porosity of 0.75. The structural schematic diagram of the gas diffusion layer is shown in Figure 3 As shown, in the figure, 1 is the inner core layer with an average diameter of 60nm, 2 is the gradient layer with a thickness of 15nm, and 3 is the outer shell layer with a thickness of 25nm.
[0036] Figure 4 The contact angle picture of the porous nanofiber gas diffusion layer. The contact angle of the commercial gas diffusion layer SGL 29BC (Figure a) is 137°, and the contact angle of the porous nanofiber gas diffusion layer prepared in this example (Figure b) is 149°, indicating that the porous nanofiber gas diffusion layer has better hydrophobicity and is more conducive to the discharge of the reactant-water.
[0037] Performance Test:
[0038] The prepared porous nanofiber gas diffusion layer was assembled into a proton exchange membrane fuel cell: a platinum-carbon catalyst (platinum catalyst loading of 0.4 mg•cm -2 ), used as the cathode of proton exchange membrane fuel cells; a platinum-carbon catalyst (platinum catalyst loading of 0.2 mg cm) was coated on a commercial gas diffusion layer SGL29BC -2 ), used as the anode of the proton exchange membrane fuel cell; then the proton exchange membrane (Nafion211 membrane) was placed between the cathode and anode, and hot-pressed at 135°C for 2 minutes to obtain MEA for packaging.
[0039] Figure 5This is the discharge performance diagram of the proton exchange membrane fuel cell assembled with porous nanofiber gas diffusion layer. The comparison sample is the performance of a single cell assembled with SGL29BC.
[0040] Discharge curve test process: Before the test, the anode and cathode are respectively introduced into fully humidified nitrogen and hydrogen for activation for 3 hours, and the activation temperature is 80°C; after activation, the cathode is introduced into fully humidified oxygen or air, and the anode is introduced into fully humidified hydrogen, and a polarization curve test is performed. During the test, each working point is maintained for 30s and 3 experimental data are taken, and the test is repeated until a repeated polarization curve is obtained.
[0041] From the battery discharge curve, it can be found that the proton exchange membrane fuel cell assembled with porous nanofiber gas diffusion layer has a high discharge current of 1000 mA•cm -2 The working voltage is 0.68V. The proton exchange membrane fuel cell assembled with SGL29BC is 1000 mA•cm -2 The operating voltage is 0.604V, indicating that the proton exchange membrane fuel cell prepared with the gas diffusion layer prepared by the present invention has a higher operating voltage at high current density, which is related to the excellent gas transmission process and liquid transmission process of the gas diffusion layer prepared by the present invention.
[0042] Example 2
[0043] A method for preparing a porous nanofiber gas diffusion layer comprises the following steps:
[0044] (1) Preparation of the core layer dispersion: 1500 mg of polyacrylic acid was weighed and dissolved in 10 mL of deionized water, stirred for 180 min, then 500 mg of perfluorosulfonic acid resin was added, stirred for 180 min, and allowed to stand for 30 min to obtain a uniform polymer solution for use; 2000 mg of acetylene black was weighed and dispersed in 10 mL of deionized water, ultrasonicated for 120 min to obtain a uniform carbon powder solution; 1.0 mL of the polymer solution and 1.0 mL of the carbon powder solution were taken, the two were mixed evenly, and stirred for 240 min to obtain a core-shell dispersion.
[0045] (2) Preparation of the shell solution: The specific method is as follows: weigh 1500 mg of polyacrylic acid and dissolve it in 10 mL of water, stir for 180 min, then add 10 mL of 60% polytetrafluoroethylene dispersion, stir for 120 min, and let stand for 30 min to obtain a shell solution.
[0046] (3) Preparation of nanofiber gas diffusion layer, as follows:
[0047] (a) Construction of nanofiber preparation device, such as Figure 1As shown, the core layer dispersion and the shell layer solution are placed in 5 mL syringes respectively, and then the syringes are placed on syringe pumps respectively to control the flow rate of the liquid in the syringe tubes; the two syringes are connected to the syringe tube 4 respectively, and then the syringe tube 4 is connected to the core-shell spinning needle 3, and then the core-shell spinning needle 3, the syringe tube 4, and the spinning needle 5 are connected, and the stabilized power supply connector is connected to the spinning needle 5;
[0048] (b) Adjust the shell injection pump flow rate to 0.6 mL•min -1 The flow rate of the nuclear layer injection pump is 0.6 mL•min -1 , then the solution in the injection tube 4 coming out of the core-shell spinning needle 3 is a mixed solution, with a carbon powder dispersion inside and a polymer solution outside. Since both the carbon powder dispersion and the polymer solution are aqueous solutions, at the interface region between the two, under the action of the concentration gradient, the carbon powder and ionomer materials diffuse from the inside to the outside, while the polytetrafluoroethylene diffuses from the outside to the inside, so that the solution entering the spinning needle 5 has a gradient distribution of hydrophobic materials from the outside to the inside. The voltage of the stabilized power supply is set to 15 kV, the distance between the spinning needle 5 and the receiver 6 is 20 cm, and a nanofiber gas diffusion layer is obtained on the surface of the receiver 6.
[0049] (4) The post-treatment operation of the nanofiber gas diffusion layer is as follows: the gas diffusion layer is placed in a sealed apparatus (structured as Figure 2 The device was heated to 80°C and nitrogen with a humidity of 80% was introduced into the instrument at a nitrogen flow rate of 200 mL min -1 , the passage time is 24h. When nitrogen containing water vapor passes through the nanofiber gas diffusion layer, liquid water is distributed along the nanofibers. Since polyacrylic acid is easily soluble in aqueous solution, the polyacrylic acid in the nanofibers will be discharged with the nitrogen, so that the nanofibers present a porous structure, that is, a porous nanofiber gas diffusion layer with a diameter of 340nm and a porosity of 0.82. The structural schematic diagram of the gas diffusion layer is shown in Figure 3 As shown, in the figure, 1 is the inner core layer with an average diameter of 180nm, 2 is the gradient layer with a thickness of 25nm, and 3 is the outer shell layer with a thickness of 55nm.
[0050] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any modifications, equivalent substitutions and improvements made by any technician familiar with the technical field within the technical scope disclosed by the present invention and within the spirit and principle of the present invention should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a porous nanofiber gas diffusion layer, characterized in that: The steps include: (1) The core layer dispersion is prepared as follows: prepare 50-150 g / L polyacrylic acid solution, stir for 30-180 min, then add ionomer powder, stir for 30-180 min, let stand for 10-30 min, and obtain a uniform polymer solution for use; prepare 100-200 g / L acetylene black dispersion, ultrasonicate for 30-180 min, and obtain a uniform carbon powder solution; mix the polymer solution and the carbon powder solution at a volume ratio of 0.5-2:0.5-1.0, and stir for 60-240 min to obtain a core layer dispersion; (2) Preparation of the shell solution: prepare 50-150 g / L polyacrylic acid solution, stir for 30-180 min, then add an equal volume of 60% polytetrafluoroethylene dispersion, stir for 30-180 min, and let stand for 10-30 min to obtain a shell solution; (3) Preparation of nanofiber gas diffusion layer, specifically as follows: build a nanofiber preparation device, place the core layer dispersion and the shell layer solution in syringes respectively, and then place the two syringes on the injection pump to control the liquid flow rate in the injection tube; connect the two syringes to the core-shell spinning needles respectively, and then connect the core-shell spinning needle, the injection tube, and the spinning needle in sequence, and connect the voltage regulator power supply connector to the spinning needle. The solution in the injection tube coming out of the core-shell spinning needle is a mixed solution, with a carbon powder dispersion inside and a polymer solution outside, and the nanofiber gas diffusion layer is obtained by electrospinning; (4) The post-treatment operation of the nanofiber gas diffusion layer is as follows: the gas diffusion layer is placed in a closed device and the temperature of the device is raised to 60-90°C; nitrogen gas with a humidity of 60-100% is introduced at a nitrogen flow rate of 30-2000 mL min -1 , the passage time is 24~48h, and a porous nanofiber gas diffusion layer is obtained.
2. The method for preparing a porous nanofiber gas diffusion layer according to claim 1, characterized in that: The electrospinning parameters in step (3) are as follows: the shell solution flow rate is controlled to be 0.02-1.5 mL min -1 , control the flow rate of the core layer dispersion to 0.02~2.5mL min -1 , set the voltage of the regulated power supply to 10~18kV, and the distance between the spinning needle and the receiver to 10~25cm.
3. The method for preparing a porous nanofiber gas diffusion layer according to claim 1, characterized in that: The ionomer in step (1) is selected from one or more of perfluorosulfonic acid resin, perfluorosulfonic acid-doped polypyrrole, perfluorosulfonic acid-doped polyaniline, sulfate-doped polypyrrole, sulfate-doped polyaniline, dodecylbenzenesulfonic acid-doped polypyrrole, dodecylbenzenesulfonic acid-doped polyaniline, and phosphotungstic acid.
4. The porous nanofiber gas diffusion layer prepared by the preparation method according to any one of claims 1 to 3.
5. A fuel cell, characterized in that: It comprises the porous nanofiber gas diffusion layer as claimed in claim 4.
Citation Information
Patent Citations
Gas diffusion layer, preparation method and metal-air battery
CN105098199A
Microporous layer material for water / gas separation and transmission as well as preparation method and application of microporous layer material
CN113921832A